(Dis)continuity and advisory challenges in farmer-led retro-innovation: biological pest control and direct marketing in Latvia. Issue 5 (20th October 2022) - Kilis, Emils; Adamsone-Fiskovica, Anda; Šūmane, Sandra; Tisenkopfs, Talis
ABSTRACT: Purpose: To advance the discussion of retro-innovation and highlight the implications this has for the provision of agricultural advice and the role of advisors. Design/Methodology/Approach: 70 interviews with farmers and 10 interviews with experts on biological pest control and direct marketing in Latvia were conducted. Findings: Biological pest control and direct marketing in Latvia are practices that challenge existing conceptions of retro-innovation as they exhibit incremental development, while still combining old and new knowledge in a way that transforms farming practices. They also underline the importance of continuous learning and exchange within the farming community, which supplement the knowledge and advice provided by formal advisory organisations, indicating that the practices are highly dependent upon locally embedded sources of knowledge and a balance between formal instruction and informal peer-to-peer learning. This allows them to retain their dynamism and evolve, although more targeted advisory assistance would help to address issues that prevent biological pest control and direct marketing from being more widely adopted. Practical implications: This paper highlights the importance of locally embedded forms of learning and advice provision. A better understanding of these can provide a more solid basis for interventions that aim to encourage widespread adoption of sustainability-oriented practices. Theoretical implications: This paper improves understanding of retro-innovation processes by drawing attention to the disparate motivations driving innovation and the role of continuity in retro-innovation. Originality: This paper advances the discussion on retro-innovation by looking at examples that expand upon existing approaches to it and highlight specific advisory challenges.